True Believers, Deserters, and Traitors: Who Leaves Insurgent Groups and Why (2015)
Anti-insurgent militias and states attempt to erode insurgent groups’ capacities and co-opt insurgent fighters by promising and providing benefits. They do so to create a perception that the insurgency is unraveling and to harness inside information to prosecute more effective counterinsurgency campaigns. Why do some insurgents defect to a paramilitary group and others exit the war by demobilizing, while still others remain loyal to their group? This article presents the first empirical analysis of these questions, connecting insurgents’ motivations for joining, wartime experiences, and organizational behavior with decisions to defect. A survey of ex-combatants in Colombia shows that individuals who joined for ideological reasons are less likely to defect overall but more likely to side-switch or demobilize when their group deviates from its ideological precepts. Among fighters who joined for economic reasons, political indoctrination works to decrease their chances of demobilization and defection to paramilitaries, while opportunities for looting decrease economically motivated combatants’ odds of defection. © 2015, © The Author(s) 2015.